EUROPEAN INTEGRATION RESEARCH: IN SEARCH OF THEORETICAL PARADIGM - Radžvilas, Vytautas (Politologija, 2015)
This article is an attempt to overview and evaluate the recent state of the theory of European integration and it’s development perspectives in the future. The abundance and variety of theoretical approaches on European integration should not be considered as self-evident and reliable indicator of the flourishment of this kind of theory. Distinct and divergent „broad“ and „narrow“ definitions of integration theory, as well as various understandings of it’s meaning and purpose should be regarded as symptoms of it‘s disintegration and fragmentation. In the absence of the broader theoretical paradigm serving as a basis and making sense of European integration research, „mosaic“, or fragmented picture of integration, unfolds and gains dominance, thus preventing the understanding of deep and long-term tendencies of the integration process and it‘s likely effects for the future of the whole continent. The reconstruction and renewal of the theoretical paradigm of European integration research through the reflective restoration of the equilibrium between theoretical “explanation” and “understanding” is the necessary prerequisite for the development and progress in this research field.